THE EFFECT OF ENTREPRENEURSHIP KNOWLEDGE ON ENTREPRENEURSHIP READINESS MEDIATED BY ENTREPRENEURSHIP MOTIVATION IN STUDENTS - Marsofiyati; Henry Eryanto; Anisa Wulandari (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the effect of entrepreneurial knowledge on entrepreneurial readiness mediated by entrepreneurial motivation in students of SMK Negeri 40 Jakarta. This research is a causal associative research with a quantitative approach and uses a survey method. The population in this study were students of Class XI SMK Negeri 40 Jakarta. The sampling technique used purposive sampling technique with certain considerations so that the population in this study was 214 students and a sample of 131 students referring to Isaac and Michael's table. The data analysis technique used in this study uses Structural Equation Modeling Partial Least Squares (SEM-PLS) which is calculated using SmartPLS version 3.0 software. The technical analysis used in this research is the analysis of the outer model, inner model and hypothesis testing where hypothesis testing has direct and indirect effects. The results of this study indicate that there is a positive and significant influence between entrepreneurial knowledge variables on entrepreneurial readiness, there is a positive and significant influence between entrepreneurial motivation variables on entrepreneurial readiness, there is a positive and significant influence between entrepreneurial knowledge on entrepreneurial motivation and there is a positive and significant influence between entrepreneurial knowledge on entrepreneurial readiness is mediated by entrepreneurial motivation.